Barriers to utilization of anganwadi services by pregnant women and lactating mothers: a hospital based cross sectional study in rural South Karnataka - Jose, Maria Jessy; Johnson, Avita Rose; Thomas, Anupa; Mendez, Delfi; Sebastian, Cristeena (International Journal Of Community Medicine And Public Health, 2019)
Background: Antenatal care and supplementary nutrition are evidence-based strategies to improve neonatal outcomes and birth weight, and are currently provided free of cost by the government in every village through the ICDS. This study aims to assess the utilization of Anganwadi services by pregnant and lactating mothers in a rural area and the various barriers to utilization of Anganwadi services. Methods: A hospital-based, cross-sectional study was conducted among pregnant women (more than 28 weeks gestation) and lactating mothers (up to 6 months after delivery) availing maternal and child health services at a maternity hospital in a rural area of Ramnagara district in South Karnataka, using a pre-tested questionnaire. Results: Awareness regarding Anganwadi services available for pregnant and lactating mothers like IFA, calcium and deworming tablets, TT and health check-ups was found to be poor. While more than half of the women had received health education from Anganwadi teacher, important topics like dangers signs, birth preparedness and essential antenatal care were not discussed. Conclusions: Utilization of health care services at the Anganwadi was poor among the subjects. Supplementary nutrition was not utilized by 54% of pregnant women and 43% of lactating mothers. Those who had been visited by Anganwadi teacher at home and those who received nutrition education by the Anganwadi teacher had significantly higher consumption of supplementary nutrition. The common barriers to utilization were lack of awareness of services and perception of poor quality and hygiene of the supplementary nutrition.